Effect of additional vitamin E and zinc supplementation on immunological changes in peripartum Sahiwal cows. Issue 6 (10th April 2014) - Chandra, G.; Aggarwal, A.; Kumar, M.; Singh, A. K.; Sharma, V. K.; Upadhyay, R. C.
Summary This study was conducted to exploit ameliorative effect of additional vitamin E and/or zinc supplementation on immune response of peripartum Sahiwal cows. Thirty‐two pregnant dry Sahiwal cows were blocked into four treatment groups (n = 8), namely control, zinc (Zn), vitamin E (Vit E) and zinc + vitamin E (Zn + Vit E). Feeding regimen was same in all the groups except that the Sahiwal cows in the zinc‐, vitamin E‐ and zinc + vitamin E‐fed groups were additionally supplemented with 60 mg Zn/kg DM, 1000 IU vitamin E and 60 mg/kg + 1000 IU Zn + vitamin E, respectively, from day 60 pre‐partum to day 90 post‐partum. Blood samples were collected on days −60, −45, −30, −15, −7, −3, 0, 3, 7, 15, 30, 45, 60, 90 and 120 with respect to day of parturition and analysed for total immunoglobulin (TIG), immunoglobulin G (IgG), interleukin‐2 (IL‐2), vitamin E (Vit E) and zinc (Zn) status. Before calving, cows showed a decrease in plasma TIG, IgG, IL‐2, Vit E and Zn levels. However, increased levels of plasma TIG, IgG, IL‐2, Vit E and Zn were observed after calving. After calving, Sahiwal cows supplemented with Zn + Vit E had higher plasma TIG, IgG and IL‐2 in comparison with cows of control and Zn + Vit E‐fed groups. In the present study, plasma vitamin E level was higher in Vit E‐fed and Zn + Vit E‐fed cows; however, zinc level was higher in Zn‐ and Zn + Vit E‐supplemented cows. In conclusion, a reduced immune response during peripartum period in Sahiwal cows was ameliorated by dietary vitamin E and zinc supplementation.